Tính
D=1+5+5^5+5^9+...+5^28
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
Bài làm
a) \(\left(\frac{3}{8}+\frac{-1}{4}+\frac{5}{12}\right):\frac{2}{3}\)
\(=\left(\frac{9}{24}+\frac{-6}{24}+\frac{10}{24}\right).\frac{3}{2}\)
\(=\frac{13}{24}.\frac{3}{2}\)
\(=\frac{39}{48}\)
b) \(\frac{-5}{7}.\frac{2}{11}+\frac{-5}{7}.\frac{9}{11}+1\frac{5}{7}\)
\(=-\frac{5}{7}.\left(\frac{2}{11}+\frac{9}{11}\right)+\frac{12}{7}\)
\(=-\frac{5}{7}.1+\frac{12}{7}\)
\(=\frac{7}{7}\)
\(=1\)
c) \(0,25:\left(10,3-9,8\right)-\frac{3}{4}\)
\(=\frac{25}{100}:\left(0,5\right)-\frac{3}{4}\)
\(=\frac{5}{4}:\frac{1}{2}-\frac{3}{4}\)
\(=\frac{5}{4}.2-\frac{3}{4}\)
\(=\frac{5}{2}-\frac{3}{4}\)
\(=\frac{10}{4}-\frac{3}{4}=\frac{7}{4}\)
d) \(-\frac{5}{9}.\frac{13}{28}-\frac{13}{28}.\frac{4}{9}\)
\(=-\frac{13}{28}\left(\frac{5}{9}+\frac{4}{9}\right)\)
\(=-\frac{13}{28}.\frac{9}{9}\)
\(=-\frac{13}{28}.1\)
\(=-\frac{13}{28}\)
A) 7/38 x 9/11 +7/38 x 4/11 -7/38 x 2/11
=7/38.(9/11+4/11-2/11)
=7/38
B) 5/31 x 21/25 + 5/31 x -7/10 - 5/31 x 9/20
=5/31.(21/25-7/10-9/20)
=5/31.(-31/100)
=-1/20
4: \(=\dfrac{2+3}{7}+\dfrac{1+6}{9}-\dfrac{5}{6}=\dfrac{5}{7}+\dfrac{7}{9}-\dfrac{5}{6}=\dfrac{83}{126}\)
5: \(=\dfrac{-5-2}{7}+\dfrac{3+1}{4}-\dfrac{1}{5}=-\dfrac{1}{5}\)
6: \(=\dfrac{-3-28}{31}+\dfrac{-6-1}{17}+\dfrac{1-5}{25}=-1-\dfrac{7}{17}-\dfrac{4}{25}=-\dfrac{668}{425}\)
4. \(\dfrac{2}{7}+\dfrac{1}{9}+\dfrac{3}{7}+\dfrac{5}{9}+\dfrac{-5}{6}\)
\(=\left(\dfrac{2}{7}+\dfrac{3}{7}\right)+\left(\dfrac{1}{9}+\dfrac{5}{9}\right)+\dfrac{-5}{6}\)
\(=\dfrac{5}{7}+\dfrac{2}{3}+\dfrac{-5}{6}\)
\(=\dfrac{30+28+\left(-35\right)}{42}=\dfrac{23}{42}\)
5. \(\dfrac{-5}{7}+\dfrac{3}{4}+\dfrac{-1}{5}+\dfrac{-2}{7}+\dfrac{1}{4}\)
\(=\left(\dfrac{-5}{7}+\dfrac{-2}{7}\right)+\left(\dfrac{3}{4}+\dfrac{1}{4}\right)+\dfrac{-1}{5}\)
\(=\dfrac{-7}{7}+\dfrac{4}{4}+\dfrac{-1}{5}\)
\(=-1+1+\dfrac{-1}{5}\)
\(=-\dfrac{1}{5}\)
6. \(\dfrac{-3}{31}+\dfrac{-6}{17}+\dfrac{1}{25}+\dfrac{-28}{31}+\dfrac{-1}{17}+\dfrac{-1}{5}\)
\(=\left(\dfrac{-3}{31}+\dfrac{-28}{31}\right)+\left(\dfrac{-6}{17}+\dfrac{-1}{17}\right)+\dfrac{1}{25}+\dfrac{-1}{5}\)
\(=\dfrac{-31}{31}+\dfrac{-7}{17}+\dfrac{1}{25}+\dfrac{-1}{5}\)
\(=-1+\dfrac{-7}{17}+\dfrac{1}{25}+\dfrac{-1}{5}\)
\(=\dfrac{-425+\left(-175\right)+17+\left(-85\right)}{425}=\dfrac{-668}{425}\)
a=113/13-(24/7+53/13)=113/13-24/7-53/13=60/13-24/7=396/16
b=(64/9+37/11)-44/9=64/9+37/11-44/9=20/9+37/11=181/33
c=-5/7(2/11+9/11)+15/7=-5/7+15/7=10/7
d=0.7.22/3.20.0.375.5/28=0
e=(6,17+35/9-236/97)(1/3-0.25-1/12)=A.(1/3-1/4-1/12)=A.(1/12-1/12)=A.0=0
e=(6,17 + 3 5/9 - 2 36/97 ) . ( 1/3 - 0,25 - 1/12)=(6,17 + 3 5/9 - 2 36/97 ) .(1/3-1/12-0,25)
=(6,17 + 3 5/9 - 2 36/97 ) .(4/12-1/12-0,25)=(6,17 + 3 5/9 - 2 36/97 ) .(3/12-0,25)
=(6,17 + 3 5/9 - 2 36/97 ) .(1/4-0.25)=(6,17 + 3 5/9 - 2 36/97 ) .(0.25-0.25)
=(6,17 + 3 5/9 - 2 36/97 ) .0=0
Vậy E=0
a) \(\dfrac{11}{3}-\dfrac{2}{3}\times\dfrac{5}{6}\)
\(=\dfrac{11}{3}-\dfrac{10}{18}\)
\(=\dfrac{11}{3}-\dfrac{5}{9}\)
\(=\dfrac{33}{9}-\dfrac{5}{9}\)
\(=\dfrac{28}{9}\)
b) \(\dfrac{13}{2}+\dfrac{7}{6}:\dfrac{2}{3}\)
\(=\dfrac{13}{2}+\dfrac{7}{6}\cdot\dfrac{3}{2}\)
\(=\dfrac{13}{2}+\dfrac{7}{4}\)
\(=\dfrac{26}{4}+\dfrac{7}{4}\)
\(=\dfrac{33}{4}\)
c) \(\dfrac{28}{9}-\dfrac{3}{4}+\dfrac{1}{3}\)
\(=\dfrac{28}{9}+\dfrac{3}{9}-\dfrac{3}{4}\)
\(=\dfrac{31}{9}-\dfrac{3}{4}\)
\(=\dfrac{124}{36}-\dfrac{27}{36}\)
\(=\dfrac{97}{36}\)
d) \(\dfrac{5}{8}:\dfrac{2}{3}\times\dfrac{1}{5}\)
\(=\dfrac{5}{8}\times\dfrac{3}{2}\times\dfrac{1}{5}\)
\(=\dfrac{15}{80}\)
\(=\dfrac{3}{16}\)
a) \(\dfrac{11}{3}-\dfrac{2}{3}\times\dfrac{5}{6}=\dfrac{11}{3}-\dfrac{5}{9}=\dfrac{28}{9}\)
b) \(\dfrac{13}{2}+\dfrac{7}{6}:\dfrac{2}{3}=\dfrac{13}{2}+\dfrac{7}{6}\times\dfrac{3}{2}=\dfrac{13}{2}+\dfrac{7}{4}=\dfrac{33}{4}\)
c) \(\dfrac{28}{9}-\dfrac{3}{4}+\dfrac{1}{3}=\dfrac{97}{36}\)
d) \(\dfrac{5}{8}:\dfrac{2}{3}\times\dfrac{1}{5}=\dfrac{5}{8}\times\dfrac{3}{2}\times\dfrac{1}{5}=\dfrac{3}{16}\)